1966 international toy fair Nuremberg 13 - 18 February - Smith, Charles E. (College of Aeronautics, 1966)
Nuremberg is a magic city. For one week each February this quaint but bustling place becomes an international wonderland. Not only is a fortune in toy business transacted but a very warm and human thing takes place. Visitors renew old associations and make new ones. Germans, Amercians, Britons, Poles, Belgians, French, Italians, Czechs, Swedes, Danes, Russians, Orientals, and others are involved in the largest display of toys in the world; and with each other, Peoples attitudes toward merchandise become stereotyped after a number of years in the toy business. But their attitudes and behavior toward their one time a year friends take on a new vitality each succeeding year. For American toy buyers the Nuremberg Spielwarenmesse (Toy Fair) offers a convenience of shopping not found elsewhere. The slick, high pressure salesmanship of New York is absent here. It is truly a buyers market. For the American toy manufacturer, Nuremberg affords 4 he opportunity to broaden his market and sources of supply as well as the chance to look for hew items, and even more important, new ideas. The exhibitions are held in five connecting buildings and there is an ample sprinkling of restaurants, snack bars, and vendors purveying the popular Nuremberg bratwurst. These are small sausages served with or without sauer- kraut and mustard. The buildings are well lit and well heated. This year these pleasant physical conditions were supplemented by unseasonably warm, clear weather.